TURNING UBUD INTO UNWTO'S PROTOTYPE FOR A WORLD GASTRONOMIC DESTINATION THROUGH GASTRODIPLOMACY - Ulung, Alessandro Kurniawan (UI Scholars Hub, 2023)
In 2019, the Indonesian Government proposed Ubud in Bali to become the United Nations World Tourism Organization (UNWTO) 's prototype for a world gastronomic destination. It turned out that, despite its rich inventory of gastronomic assets and attractions, Ubud met with challenges when convincing UNWTO to give it the title. To deal with this problem, the Indonesian Government practised gastrodiplomacy to influence UNWTO to endorse Ubud as the world gastronomic destination. This research, therefore, aims to explain the implementation of Indonesia's gastrodiplomacy. By using a qualitative method with interpretative analysis in place, I argued that the Government used gastrodiplomacy to introduce diverse culture, history and tradition behind Balinese culinary delights, including the story about the spice trail, and used them as soft power to convince UNWTO that Ubud had ticked all the criteria of the world gastronomic destination. The Government saw the spice trail story as the strength of Ubud's gastronomic tourism because it can explain why Balinese dishes are rich in flavour, cultural and historical values. The Government also invited non-state actors to take part in the project. Though they did different strategies for implementing gastrodiplomacy, their collaboration strengthened Indonesia's gastrodiplomacy in convincing UNWTO to promote Ubud as the world gastronomic destination.